2020
DOI: 10.1155/2020/2853650
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Stem Cell Therapy for Spinal Cord Injury

Abstract: Background. Spinal cord injury (SCI) is one of the serious neurological diseases that occur in young people with high morbidity and disability. However, there is still a lack of effective treatments for it. Stem cell (SC) treatment of SCI has gradually become a new research hotspot over the past decades. This article is aimed at reviewing the research progress of SC therapy for SCI. Methods. Review the literature and summarize the effects, strategies, related mechanisms, safety, and clinical application of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 181 publications
0
50
0
1
Order By: Relevance
“…Stem cell therapy has been widely studied in different central nervous system diseases (such as autoimmune encephalomyelitis, spinal cord injury, and stroke) in recent 20 years [6][7][8]. There are many types of stem cells, including embryonic stem cells, neural stem cells, hematopoietic stem cells, and mesenchymal stem cells [9]. As early as 1970, Friedenstein et al cultured fibroblast precursor from the cell suspension of guinea pig spleen and bone marrow, which is now called mesenchymal stem cell [10].…”
Section: Introductionmentioning
confidence: 99%
“…Stem cell therapy has been widely studied in different central nervous system diseases (such as autoimmune encephalomyelitis, spinal cord injury, and stroke) in recent 20 years [6][7][8]. There are many types of stem cells, including embryonic stem cells, neural stem cells, hematopoietic stem cells, and mesenchymal stem cells [9]. As early as 1970, Friedenstein et al cultured fibroblast precursor from the cell suspension of guinea pig spleen and bone marrow, which is now called mesenchymal stem cell [10].…”
Section: Introductionmentioning
confidence: 99%
“…Transplanted stem cells show anti-apoptotic effects by disturbing the balance between anti-apoptotic and pro-apoptotic factors and, thus, improving the survival of the tissue and enhancing neurological function resumption. They also exhibit anti-inflammatory effects by reducing the number of neutrophils and the expression of inflammatory proteins that upgrade the neurological function [25].…”
Section: Therapeutic Mechanisms Of Stem Cellsmentioning
confidence: 99%
“…MSCs were also capable of triggering the electrophysiological features of neurons which means that MSCs have neuronal replacement potentials [156][157][158]. Furthermore, some studies observed cosecretion of markers from distinctive neural lineages in the same cells [156,159,160]. Transplanted MSCs were also able to trigger high levels of transforming growth factor-β (TGF-β) (Table 1) which was able to lessen the formation of scar tissue [4,161,162].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%